2020
DOI: 10.1007/s40822-020-00160-3
|View full text |Cite
|
Sign up to set email alerts
|

How have the European central bank’s monetary policies been affecting financial markets in CEE-3 countries?

Abstract: This paper aims to contribute to the growing pool of literature on the spillover effects of the European Central Bank’s (un)conventional monetary policies on the exchange rate, sovereign bond and equity markets of the Czech Republic, Hungary and Poland (CEE-3 countries), which are collectively known as the CEE-3 countries. The study is conducted using daily data from January 2010 to September 2019. Our results indicate that the financial markets of the CEE-3 countries have been strongly influenced by the nonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
3
0
1
Order By: Relevance
“…The focus on the response of the sovereign bond yields, exchange rates, and stock market indexes to policy events has been a common practice in the related literature (cf. Georgiadis and Gräb, 2016 ; Grabowski and Stawasz-Grabowska, 2021 ; Sever et al, 2020 ). The important difference we make is the use of the NEER instead of the nominal exchange rate vis-à-vis one of the global reserve currencies (usually the euro in the case of CE countries).…”
Section: Methodsmentioning
confidence: 99%
“…The focus on the response of the sovereign bond yields, exchange rates, and stock market indexes to policy events has been a common practice in the related literature (cf. Georgiadis and Gräb, 2016 ; Grabowski and Stawasz-Grabowska, 2021 ; Sever et al, 2020 ). The important difference we make is the use of the NEER instead of the nominal exchange rate vis-à-vis one of the global reserve currencies (usually the euro in the case of CE countries).…”
Section: Methodsmentioning
confidence: 99%
“…Lettau and Ludvigson ( 2001 ) argued that the ratio of consumption to the aggregate wealth, including labor income, is important to the change in stock prices. Grabowski and Stawasz-Grabowska ( 2021 ) also found that the European Central Bank’s monetary policy also affected the equity markets of the Czech, Hungary, and Poland.…”
Section: Literature Reviewmentioning
confidence: 95%
“…This may also produce externalities for local bond markets and have an impact on domestic economies (Kolasa and Wesołowski, 2020). There is now accumulating evidence that a substantial part of spillovers from the ECB's monetary policy, both standard and non-standard one, is transmitted to CE economies via sovereign bond yields (Grabowski and Stawasz-Grabowska, 2020;Janus, 2020). Hence, the detailed evidence on the long-term interest rates is of sheer importance to policymakers in the CE countries, because exogenous movements in these yields may hamper the ability to influence interest rates on the longer end of the yield curve.…”
Section: Related Literaturementioning
confidence: 99%